A facile approach to achieve multifunctional polyethylene terephthalate fabrics with durable superhydrophobicity, photocatalysis and self-quenched flame retardance. (12th August 2020) - Lan, Yanrong; Wang, Yingchun; Zhang, Han; Shan, Peng; Shi, Xiaomeng; Long, Mengying
Abstract : Multifunctional PET fabrics were fabricated through combing layer-by-layer and spray coating methods. Abstract : Reports about polyethylene terephthalate (PET) fabrics with durable superhydrophobicity and flame retardance are very limited. In this paper, durable superhydrophobic, photocatalytic, flame-retardant (FR) PET fabrics were fabricated for the first time by a green approach and further employed for various applications. Through layer-by-layer (LBL) alternate deposition of mixed polyelectrolytes, including branched poly(ethylenimine) (BPEI), phytic acid (PA), and ammonium polyphosphate (APP), the fabric obtained superior self-quenched flame retardance through deposition of only two bilayers (BL). The fire burned very slowly, and was self-extinguished after ignition for 8 s. The fabric was also anti-dripping. When the FR fabric was further coated with a layer of PDMS-grafted-TiO2 @PDMS coating, it presented excellent superhydrophobicity and self-cleaning properties both under air and water conditions. Moreover, the final fabric showed durable superhydrophobicity, which presented resistance to repeated rinsing treatments, repeated peeling by adhesive tape, and cyclic abrasion treatments. This fabric also showed superior photocatalysis capability and photocatalytically stable superhydrophobicity. The finally coated fabrics could selectively and highly efficiently remove polluted oils from water and separate oil–water mixtures. This multifunctional fabric is believed to show very promising application potential in the flame retardance, superhydrophobicity, self-cleaning, water purification, liquid separation, and photocatalysis fields.